2020
DOI: 10.1021/acs.inorgchem.0c02754
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Binding to PBT2 Differs from That of Other 8-Hydroxyquinoline Chelators: Implications for the Treatment of Neurodegenerative Protein Misfolding Diseases

Abstract: PBT2 (5,7-dichloro-2-[(dimethylamino)­methyl]-8-hydroxyquinoline) is a small Cu­(II)-binding drug that has been investigated in the treatment of neurodegenerative diseases, namely, Alzheimer’s disease (AD). PBT2 is thought to be highly effective at crossing the blood–brain barrier and has been proposed to exert anti-Alzheimer’s effects through the modulation of metal ion concentrations in the brain, specifically the sequestration of Cu­(II) from amyloid plaques. However, despite promising initial results in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 66 publications
1
21
0
1
Order By: Relevance
“…We previously found the EXAFS of a solution of excess PBT2:Cu­(II) to be best fitted to a distorted 4-coordinate Cu­(II)- bis -PBT2 coordination environment with two pyridine nitrogen ligands and two phenol oxygen ligands . Additionally, we previously found the EXAFS of a solution of equimolar Aβ(1–42) and Cu­(II) at pH 7.4 to be best fitted to an average Cu­(II) coordination environment consisting of two histidine nitrogens and two additional oxygen or nitrogen ligands .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously found the EXAFS of a solution of excess PBT2:Cu­(II) to be best fitted to a distorted 4-coordinate Cu­(II)- bis -PBT2 coordination environment with two pyridine nitrogen ligands and two phenol oxygen ligands . Additionally, we previously found the EXAFS of a solution of equimolar Aβ(1–42) and Cu­(II) at pH 7.4 to be best fitted to an average Cu­(II) coordination environment consisting of two histidine nitrogens and two additional oxygen or nitrogen ligands .…”
Section: Resultsmentioning
confidence: 97%
“…In conventional K-edge XAS, the short lifetime of the 1s core hole causes spectral broadening and consequent loss of detail and chemical sensitivity. As described previously, Cu K-edge HERFD-XAS uses the Cu Kα 1 fluorescence line and observes a small subset of the 2p 3/2 → 1s transitions that produce the Cu Kα 1 fluorescence, eliminating most of the lifetime broadening from the 1s core hole and improving the spectral resolution.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, it has low selectivity for metal ions [ 152 ]. An advanced compound, PBT2, mainly binds to excess copper and zinc and possibly iron in the brain, thereby reducing the number of amyloid plaques and relocating these metal ions to the depleted cell and neuron compartments [ 145 ].…”
Section: Treatment Strategies Using Iron Chelatorsmentioning
confidence: 99%
“…92 The PBT2 can form (bi-or tri-dentate) complex with Cu 2+ and demonstrated good brain penetration and good ability to sequestrate Cu 2+ from Aβ plaque. 90,140 This more structural flexibility is related to an ability of the compound to form tri-dentate complex with Cu 2+ ion which could contribute to its superior ionophoric activity beyond that of the CQ. 87 More promising anti-AD effect of the PBT2 also may be due to its potential to form bi-/tri-dentate complex with many possible Cu 2+ -binding ligand such as phenolic oxygen, tertiary amine nitrogen, and pyridine nitrogen.…”
Section: Cq and Pbt2 (Cu Zn And Fe Chelators)mentioning
confidence: 99%
“…87 More promising anti-AD effect of the PBT2 also may be due to its potential to form bi-/tri-dentate complex with many possible Cu 2+ -binding ligand such as phenolic oxygen, tertiary amine nitrogen, and pyridine nitrogen. 87,140 In vivo study showed that oral administration of PBT2 decreased Aβ aggregation and oligomerization in AD mice models. 87 Clinical trial phase IIa demonstrated beneficial effect on AD patients.…”
Section: Cq and Pbt2 (Cu Zn And Fe Chelators)mentioning
confidence: 99%